2008
DOI: 10.2139/ssrn.1105640
|View full text |Cite
|
Sign up to set email alerts
|

Specification Analysis of Structural Credit Risk Models

Abstract: In this paper we conduct a specification analysis of structural credit risk models, using term structure of credit default swap (CDS) spreads and equity volatility from high-frequency return data. Our study provides consistent econometric estimation of the pricing model parameters and specification tests based on the joint behavior of time-series asset dynamics and cross-sectional pricing errors. Our empirical tests reject strongly the standard Merton (1974) model, the Black and Cox (1976) barrier model, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 39 publications
(1 reference statement)
1
11
0
Order By: Relevance
“…We set α = 60%. Huang and Zhou (2008) find that in a sample of firms the average payout rate is 2.14%, and, more specifically, the average for BB-rated firms is 2.15% and for A-rated firms is 2.02%. Given the small variation across different ratings, we use δ = 2% throughout the paper.…”
Section: Debt Structurementioning
confidence: 86%
“…We set α = 60%. Huang and Zhou (2008) find that in a sample of firms the average payout rate is 2.14%, and, more specifically, the average for BB-rated firms is 2.15% and for A-rated firms is 2.02%. Given the small variation across different ratings, we use δ = 2% throughout the paper.…”
Section: Debt Structurementioning
confidence: 86%
“…Using a maximum likelihood estimation procedure, they found that the asset process for both individual stocks and the indexes of the S&P-500 and the NASDAQ with jumps having double-exponential distribution performs better than the case with normally distributed jumps or without jumps. There are a number of works that study the double-exponential jump diffusion model; see Kou (2002), Kou and Wang (2003), (2004), Huang and Huang (2003), and Huang and Zhou (2008), to name only a few. Intuitively, jumps of the firm's value process are triggered if unexpected information or events are revealed, and there might be a variety of information.…”
Section: Introductionmentioning
confidence: 99%
“…5 An alternative framework to the latent factor model employed in this paper is to use a structural model approach in which credit spreads are determined by a number of structural factors suggested by theory such as interest rates, leverage and asset volatility (Collin-Dufresne and Goldstein 2001; Leland and Toft 1996;Longstaff and Schwartz 1995). Structural models are widely used in credit risk modelling; yet empirical tests suggest that structural models typically cannot accurately explain credit spreads (Eom et al 2004;Huang and Zhou 2008). 6 Relatedly, the empirical literature finds that changes in credit spreads are even harder to explain by structural factors than levels Zhang et al 2009).…”
Section: Removing Common Shocksmentioning
confidence: 99%